Kultur Antera untuk Mendukung Program Pemuliaan Tanaman Padi - Iswari S. Dewi; Bambang S. Purwoko (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2001)
The Objectives of rice breeding program in Indonesia is to obtain high yielding varieties, tolerant, resistant to abiotic and biotic stress and appropriate to planting system in specific area. To accelerate the obtainment of the varieties, a combination of conventional and no conventional breeding method can be used. One alternative procedure is anther culture. Doubled haploid lines can be obtained through cholchicine treatment or rattooning of haploid plants. Plants with high heterozygositas (F1 or F2) can be used as anther source to obtain genetic variability of doubled haploid plants. High degree of homozigousity can be obtained at the first (DHO) generation of doubled haploid plants, less than on year. Evaluation of agronomic characters follows m DHI and DH2 generations. Compared to conventional methods, the use of anther culture in rice breeding program has several advantages including efficiency of selection process, reduction of cost, time and labor. Effort to optimize anther culture method and its rize in rice breeding program in Indonesia is discussed. Key words: Anther culture, Rice